Perceptions of HIV-Related Stigma in Portugal Among MSM With HIV Infection and an Undetectable Viral Load - Pereira, Henrique (2018)
We explored perceptions of HIV-related stigma using a qualitative approach based on the findings of in-depth e-mail asynchronous interviews with 37 self-identified Portuguese men who have sex with men (MSM) with HIV infection and undetectable viral loads. Participants were asked to answer an online interview. Major findings concerned external perceptions of HIV-related stigma, HIV status disclosure, the impact of HIV on everyday life, the presence of double discrimination, and general perceptions of HIV-related stigma. Results revealed (a) stigmatizing and discriminatory behaviors and practices in psychosocial and inter-relational events, but not in accessing and receiving health care; (b) double exposure to stigma associated with being gay and having HIV; and (c) undetectability as an autonomous identity with important connections to social and interpersonal interactions. An important implication was related to multilevel risk perceptions and the psychosocial complexity and challenges of HIV infection. In Portugal, HIV is still a socially disabling disease.